Mukhang maarte - Atienza, Glecy C. (Glecy Cruz) (Manila, Philippines : UST Pub. House, 2003)
Literary works on sociocultural life in the Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: Philippine literature -- 20th century -- History and criticism; Philippines -- In literature; Philippines -- Social life and customs